Determinan Multidimensional Prestasi Atlet Tenis Meja: Systematic Literature Review Dan Agenda Pengembangan Model Kinerja Atlet Berbasis Pendekatan Biopsikososial - Hasnah Hasnah (Universitas Cahaya Prima, 2025)
Background: Table tennis athlete performance is shaped by a complex interaction of biological, psychological, and social factors. However, existing research has largely examined these dimensions in isolation, leaving a gap in holistic performance models applicable to the sport. Objective: This systematic literature review aims to identify, synthesize, and map multidimensional determinants of table tennis athlete performance based on a biopsychosocial approach and to formulate an agenda for developing an integrated athlete performance model. Method: A systematic search was conducted across five major databases—PubMed, Scopus, Web of Science, SPORTDiscus, and Google Scholar—using PRISMA 2020 guidelines. A total of 40 studies published between 2015 and 2024 were included after applying inclusion and exclusion criteria. Studies were assessed for quality using the Mixed Methods Appraisal Tool (MMAT). Results: Three principal determinant clusters were identified: (1) biological factors including physiological capacity, anthropometry, biomechanics, and motor skills; (2) psychological factors including mental toughness, attention, motivation, and coping strategies; and (3) social factors including coaching quality, family support, peer dynamics, and socioeconomic context. An integrative biopsychosocial performance model was proposed, incorporating cross-domain interactions. Conclusion: No single-factor model is sufficient to explain table tennis performance. Future research should prioritize longitudinal designs and cross-cultural validation of the proposed integrated model.